Jogos pedagógicos no processo de ensino-aprendizagem do aluno com deficiência intelectual - Oliveira, Andréa da Silva (2022)
This research studies the usage of games as a didactic-pedagogical resource of teaching practice from the perspective of inclusive education, as a tool for the effectiveness of the teaching-learning process and in the cognitive, motor and affective development of those with Intellectual Disabilities (DI) in a municipal public school from Boa Vista-PB, in the academic year of 2021. For this, we make use of a speech through the use of oral and written narratives of Elementary School teachers, in order to understand how pedagogical games favor learning and contribute to the intellectual, cognitive and motor development of students. For the methodology, we followed a qualitative, exploratory approach, taking into account the atypical school period experienced by school institutions in times of social isolation caused by the COVID-19 pandemic. As data collection instruments, a semi-structured online questionnaire was used, directed to 13 Elementary School teachers in the final years, and a semi-structured interview, made by the WhatsApp application, with eight Elementary School teachers in the initial years. For the theoretical basis of this study, we followed the schemes of Silva (1987), Mantoan (2001, 2004, 2006, 2008, 2015), Sassaki (2003, 2005, 2008), Vygotsky (1998), Piaget (1973, 1975, 1985, 1998 and 2007), Wallon (1968, 1995), Lemos (2009), Kishimoto (1993, 1995, 1998, 2005, 2010), Antunes (1998), Luckesi (2014), Aranha (1995, 2001, 2004) among others. With the collection and discussion of data, it was observed that teachers are aware of the importance of practices with games as a fundamental pedagogical resource for the development of student learning, since they are tools that offer appropriate activities for the development of their abilities and skills. Through this research, it was understood that the methodological strategies used as pedagogical practices can contribute to the success of the teaching-learning process, both for students with DI and for students without disabilities, in order to evidence an educational practice that makes inclusion effective. From the information obtained and the investigations about the use of pedagogical games as a teaching strategy, especially for students with ID, the educational product of this research was built, which consists of a Chest of Pedagogical Games, with ten games, with different objectives, which will help teachers in their pedagogical practice.